Soil Carbon Sequestration in the Context of Climate Change Mitigation: A Review - Rodrigues, Cristina I. Dias; Brito, Luís Miguel; Nunes, Leonel J. R. (Soil systems, 2023)
This review article aims to acknowledge the multifaceted functions of soil, and given its status as the largest terrestrial carbon store, to reaffirm its previously established importance in carbon sequestration. The article outlines the key variables that affect soil’s ability to trap carbon and highlights the significance of soil in halting climate change. A bibliometric study of seven sets of keywords relating to the significance of soil in carbon sequestration for climate change mitigation laid the foundation for this review. The literature review that followed, which was based on the bibliometric analysis, concentrated on carbon sequestration and the impact of the key factors that affect the amount of organic carbon in soil, including (1) climatic conditions; (2) topography; (3) parent material; (4) organisms; and (5) soil qualities. The goal of this review article is to recognize the diverse roles of soil, while reasserting its well-documented significance in carbon sequestration. This is particularly important considering soil’s position as the largest terrestrial storehouse of carbon.